PENGARUH PENGUNGKAPAN ENVIRONMENTAL COST DAN CORPORATE SOCIAL RESPONSIBILITY TERHADAP PROFITABILITAS PERUSAHAAN MANUFAKTUR SEKTOR INDUSTRI DASAR DAN KIMIA YANG TERDAFTAR PADA BURSA EFEK INDONESIA PERIODE TAHUN 2018-2022 - Ade Widiyanti; Salsabila Dhia Shafa; Niken Kusumawardani (Jurnal Akuntansi dan Keuangan (JAK), 2024)
This study aims to evaluate the impact of environmental cost disclosure and corporate social responsibility (CSR) on the profitability of manufacturing companies in the basic and chemical industries listed on the Indonesia Stock Exchange (IDX) during the period 2018-2022. Utilizing a quantitative approach with data analysis through Eviews software, the research explores the effects of these variables on company profitability. The findings reveal that environmental cost disclosure does not have a significant effect on company profitability. The level of environmental cost allocation does not influence market reactions or investor interest in the company. Conversely, CSR has a positive impact on profitability. CSR is seen as providing a positive signal to investors as it demonstrates the company’s responsibility towards its operational impacts. Simultaneously, the independent variables, namely environmental cost disclosure and CSR, significantly affect profitability, indicating that while environmental cost disclosure does not have a direct impact, CSR plays a crucial role in enhancing company profitability and attracting investor attention. This study aims to provide insights into how environmental cost disclosure and CSR affect company financial performance and how companies can leverage this information for strategic advantages in the capital market.